Topic-Centered Aggregation of Presentations for Learning Object Repurposing - Narayanan, A/L N. Kulathu Ramaiyer; Bilal, Zaka; Balker, Wolf-Tilo; Maurer, Hermann (Advancement of Computing in Education (AACE), 2008)
Large collections of learning content, developed using applications such as Microsoft PowerPoint can be found in numerous institutions and organizations. The reusability of such custom-made learning content are however not supported in traditional applications. There is a need to annotate the available learning objects with suitable meta-data at various level of granularity. This paper investigates the provision of a tool that allows users to compare and efficiently repurpose presentations collected in some institution’s content repository. Our preliminary experiments have shown that it is indeed possible to extend the reusability of learning objects beyond its originally intended usage. By adopting a layered approach of similarity checking, topic-centered content aggregation and repurposing has been achieved. The prototype system has also shed insights on the much-needed support mechanisms for the on-the-job, incremental elicitation of metadata.